Electromagnetic tracking in image‐guided laparoscopic surgery: Comparison with optical tracking and feasibility study of a combined laparoscope and laparoscopic ultrasound system. Issue 11 (19th October 2018) - Xiao, Guofang; Bonmati, Ester; Thompson, Stephen; Evans, Joe; Hipwell, John; Nikitichev, Daniil; Gurusamy, Kurinchi; Ourselin, Sébastien; Hawkes, David J.; Davidson, Brian; Clarkson, Matthew J.
Abstract : Purpose: In image‐guided laparoscopy, optical tracking is commonly employed, but electromagnetic (EM) systems have been proposed in the literature. In this paper, we provide a thorough comparison of EM and optical tracking systems for use in image‐guided laparoscopic surgery and a feasibility study of a combined, EM‐tracked laparoscope and laparoscopic ultrasound (LUS) image guidance system. Methods: We first assess the tracking accuracy of a laparoscope with two optical trackers tracking retroreflective markers mounted on the shaft and an EM tracker with the sensor embedded at the proximal end, using a standard evaluation plate. We then use a stylus to test the precision of position measurement and accuracy of distance measurement of the trackers. Finally, we assess the accuracy of an image guidance system comprised of an EM‐tracked laparoscope and an EM‐tracked LUS probe. Results: In the experiment using a standard evaluation plate, the two optical trackers show less jitter in position and orientation measurement than the EM tracker. Also, the optical trackers demonstrate better consistency of orientation measurement within the test volume. However, their accuracy of measuring relative positions decreases significantly with longer distances whereas the EM tracker's performance is stable; at 50 mm distance, the RMS errors for the two optical trackers are 0.210 and 0.233 mm, respectively, and it is 0.214 mm for the EM tracker; at 250 mm distance, the RMS errors for the two optical trackers become 1.031 and 1.178 mm, respectively, while it is 0.367 mm for the EM tracker. In the experiment using the stylus, the two optical trackers have RMS errors of 1.278 and 1.555 mm in localizing the stylus tip, and it is 1.117 mm for the EM tracker. Our prototype of a combined, EM‐tracked laparoscope and LUS system using representative calibration methods showed a RMS point localization error of 3.0 mm for the laparoscope and 1.3 mm for the LUS probe, the lager error of the former being predominantly due to the triangulation error when using a narrow‐baseline stereo laparoscope. Conclusions: The errors incurred by optical trackers, due to the lever‐arm effect and variation in tracking accuracy in the depth direction, would make EM‐tracked solutions preferable if the EM sensor is placed at the proximal end of the laparoscope.